"C" leadership : a new way to beat the competition and manage organization stakeholders - Spina, James D.; Spina, Lori J. (Emerald Publishing Limited, 2021)
Success is envisioned as beating the competition to generate a financially strong and profitable organization while building stakeholder satisfaction. "C" Leadership style is a new management theory derived from the research and science leading to the unification of conflicting traditional leadership models. Presenting a unique approach to address the needs of all stakeholders as they contribute to the success of the organization, "C" Leadership unifies task-centered styles with people-centered styles for managing talent. Authors Jim and Lori Spina bring a track record of success and achievement in the fields of Education, Consulting and Business. Their "C" Leadership: A New Way to Beat the Competition and Manage Organization Stakeholders introduces this revolutionary and unique leadership style management system, offering a strategy geared to beat the competition by addressing the needs of all stakeholders who contribute to the success of the organization.